Capillary and venous blood glucose of healthy dogs: measurement by electrochemical method versus enzymatic laboratory - Ferreira, Patricia Almeida; Mueller, Eduardo Negri; Fischer, Elisângela Coelho; Tillmann, Mariana Teixeira; Peres, William; Nobre, Márcia de Oliveira (Semina: Ciências Agrárias, 2013)
Glucose evaluation with glucometer is important due to its high speed and low cost, being an important instrument to control glycemia alterations and allowing quick diagnostic and therapeutic decisions. In this work we have measured and compared the glycemia of capillary and venous blood of healthy dogs through digital glucometer, using, as reference, the values obtained by laboratorial enzymatic method with samples of venous blood. It was evaluated the glycemia of twenty dogs, of no specific breed, fasting for 12 hours. To evaluate the glycemia, with digital glucometer, it was used one blood drop from the ear's border and cephalic vein, while for the evaluation through laboratorial enzymatic method it was collected 2 mL of blood from the cephalic vein. The glycemia average values, obtained by digital glucometer, from venous and capillary blood were, respectively, 84,60 mg/dL (± 11,15) and 76,65 mg/ dL (± 10,73), while the ones obtained from laboratorial enzymatic method were 80,7 mg/dL (± 9,97), with no statistical differences. It is concluded that the glucometer can be securely used in dogs, since the average values of capillary and venous glycemia, measured with portable digital glucometer, were similar to the values obtained by laboratorial method.